Tomato Leaf Curl and Tomato Yellow Leaf Curl Disease and Its Management in Oman - Haq, Qazi Mohd. Imranul; Al-Amri, Issa Sulaiman; Harrasi, Ahmed Sulaiman Fadhil Al; Wadair, Ali Said Saleh Awlad (International Journal of Membrane Science and Technology, 2023)
The tomato (Solanum lycopersicum) is one of the most significant food crops in the tropics and subtropics. In recent years, invasive pests and diseases have severely damaged tomatoes in the Middle East. Begomoviruses are a plant pathogen spread by the whitefly (Bemisia tabaci gen.) with a circular single-stranded DNA (ssDNA) genome belonging to the family Geminiviridae. Oman is a source of legume viruses, which cause significant yield loss in various Omani crops, particularly tomatoes. In this review, we discuss outbreaks of tomato leaf curl disease (TLCD) and tomato yellow leaf curl disease (TYLCD) caused by the tomato leaf curl virus (TLCV) and tomato yellow leaf curl virus (TYLCV) in Oman and their controls.